SIMULASI KREATIF DALAM PEMBELAJARAN MENULIS DI KELAS II SEKOLAH DASAR - - Suwarjo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
The purpose of this classroom action research was to improve writing teaching quality at grade two of elementary school level. Teaching pattern developed was a creative simulation. The results showed that through the creative simulation students of grade two (elementary schools) had a competency in complementing a story with distinct words and simple sentences. Students’ comprehension and skill acquired from cycle to cycle significantly improved.